PENGARUH PEMBINAAN DAN DISIPLIN KERJA TERHADAP SEMANGAT KERJA GURU DAN PEGAWAI PADA SMA NEGERI 3 SIBOLGA - Karbon, Renny; Tambunan, Yenni Sofiana; Lubis, Rifka Hadia (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2023)
The formulation of the problem in this research is whether coaching and work discipline have a positive and significant effect on the morale of teachers and employees at SMA Negeri 3 Sibolga. This study aims to determine the effect of coaching and work discipline on employee morale at SMA Negeri 3 Sibolga. The sample in this study were all teachers and employees of SMA Negeri 3 Sibolga, totaling 64 (sixty four) people. The type of research used in this research is the survey method, which is the method used to obtain data from certain natural places and the research collects data through observation, distribution of questionnaire documentation and interviews. The data analysis technique in this study is Multiple Linear Regression.The results of this study indicate: Coaching partially has a positive and significant effect on the morale of teachers and employees; Work discipline partially has a positive and significant effect on the morale of teachers and employees; Coaching and Work Discipline partially have a positive and significant effect on the morale of teachers and employees